The Movement of Housing Debtors in Chile (2003-2014); O movimento de devedores e devedoras Habitacionais no Chile (2003-2014); El movimiento de deudoras y deudores habitacionales de Chile (2003-2014) - Braithwaite-Castillo, S (Universidad de Antioquia, 2026)
In the first decade of the 21st century, the Movement of Housing Debtors in Chile, led by low-income female heads of household, emerged on the public agenda to defend their homes. Over ten years, it secured benefits for more than 400,000 families and eliminated the debt requirement for access to social housing through strong female leadership. Through analysis of protest events and interviews with movement leaders, this study shows how the movement redefined housing demands and helped open a new cycle of social movements. © (2026), (Universidad de Antioquia). All right reserved.